Bioluminescence imaging of G protein-coupled receptor activation in living mice. Issue 1 (December 2017) - Kono, Mari; Conlon, Elizabeth; Lux, Samantha; Yanagida, Keisuke; Hla, Timothy; Proia, Richard
Abstract G protein-coupled receptors (GPCRs), a superfamily of cell-surface receptors involved in virtually all physiological processes, are the major target class for approved drugs. Imaging GPCR activation in real time in living animals would provide a powerful way to study their role in biology and disease. Here, we describe a mouse model that enables the bioluminescent detection of GPCR activation in real time by utilizing the clinically important GPCR, sphingosine-1-phosphate receptor 1 (S1P1 ). A synthetic S1P1 signaling pathway, designed to report the interaction between S1P1 and β-arrestin2 via the firefly split luciferase fragment complementation system, is genetically encoded in these mice. Upon receptor activation and subsequent β-arrestin2 recruitment, an active luciferase enzyme complex is produced, which can be detected by in vivo bioluminescence imaging. This imaging strategy reveals the dynamics and spatial specificity of S1P1 activation in normal and pathophysiologic contexts in vivo and can be applied to other GPCRs. G protein-coupled receptors are involved in numerous physiological functions, thus, they represent potential pharmaceutical targets. Here Kono et al. describe a new mouse model to image GPCR activation in real-time by exploiting firefly split luciferase fragment complementation that can be detected by bioluminescence imaging.